Ecoturismo e turismo de base comunitária na comunidade de Forte Velho, PB: diagnóstico e proposições - Almeida, Antonio Rafael Barbosa de (2016)
The tourism, as a practice tied to the capital, has presented capacity to reorganizing itself around milder and more acceptable proposals of consumption of the local environment and culture, with the perspective of legitimating the expansion of its activities. The environmental friendly tourism, understood within this project as a segment or category of tourism, and the Tourism of Community Base (also known as TBC), a proposal of organizing its practice, can be seen as response, whether intentional or not, of subjects like sustainable development, nature preservation, inclusion and reduction of poverty being internalized. Even though the community participation in the tourism, specially the sort done at conserved natural environments, is not really recent, the management of the initiatives that centralize the local agents as main characters of the process of stimulating, of planning and of the touristic practice has been being outlined only over the last two decades in the Country. The promoting of the community experiences in tourism has allowed income generation and the overcoming poverty through the means of this activity, at the same time it also includes the demands regarding the conserving of the local environment. The community of Forte Velho, Santa Rita-PB, gathers attractions that would raise the debate regarding the touristic practice at that area, articulating measures for community insertion within this proposal. This project has as general objective to diagnose the touristic activities done at the Forte Velho community and it's surrounding area – a region inserted at the estuary of the Paraíba River – and verify the perspective of including proposals related to the environmental friendly tourism and the Tourism of Community Base in this area. Based on a qualitative approach, interviews were done with eight community residents, those were selected by a criteria of accessibility, with distinct profiles, with the goal of understanding the local reality from land, social, cultural, environmental and economic matters. After that, the community was invited to take part in workshops focused on participation diagnosys of tourism in the studied area as per oriented by Salvati (2003) and of the International Labor Organization - ILO (2011), which allowed to explain how the tourism was seen through the light of that sample: which was the main deficiencies and benefits generated, and also make it possible the recording of the local touristic offer through inventory. Even though it includes the conflicts and frail points present within the community, from the obtained results, the feasibility and its possibility of the TBC can be seen. In order for it to come true, however, some reservations and suggestions are presented to the residents interested in articulating the measures which bring the community base and the tourism that already takes part in the area closer.